The Effect of Science Attitudes toward Science Process Skills of Junior High School Students in Jambi - Perdana, Rahmat; Asrial, Asrial; Maison, Maison (Jurnal Pendidikan MIPA, 2022)
The purpose of the research will be to see if there is an influence between students' attitudes and science process skills. Quantitative study with a sample size of 139 students. The research instrument used a questionnaire and an observation sheet. Based on the research results, there are 65.0% of students have very good attitudes in learning science and 64.3% of students' science process skills are categorized as very good. Based on the results obtained, it is known that there is an influence of students' attitudes on students' science process skills. As much as 75.7% of students' process skills in science learning are influenced by students' attitudes and 24.3% of students' science process skills are influenced by other factors. These science process skills can be trained and improved through hands-on experience such as conducting experiments or practicums. Students' science process skills will be good along with a good attitude in learning. Keywords: science attitude, science process skills, junior high school students. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp360-372